Teachers’ Innovation on Reflective and Integrative (RAI) Video Lessons in Enhancing the Academic Performance of Grade 2 Learners in Araling Panlipunan - Mary Shane Mariano; Mariefe Escalaw; Eder Gallego (JPAIR Institutional Research Journal)
This research used a quasi-experimental research design during COVID-19 distance education. It utilized a comparison and experimental group of learners at Parian Elementary School, Schools Division of Calamba City. Based on the results of the study, there is evidence to support that the experimental group performed better than the comparison group in the formative test. Likewise, the result of the Independent Samples t-test result reveals a significant difference between the Posttest Mean Scores of the Comparison and Experimental groups. Hence, the hypothesis, which states no significant difference, is rejected. Further, there is an improvement in the score of the comparison group from the pretest to posttest. However, a great improvement in the mean score of the experimental group. In conclusion, the Reflective and Integrative (RAI) video lessons successfully enhance the academic performance of Grade 2 Araling Panlipunan learners. The study recommends that Education Officials and School Administrators are encouraged to support the teachers in implementing technological pedagogical innovations in delivering 21st-century quality education. They are also encouraged to conduct seminars and workshops on technological pedagogical innovation in the new normal education. Future researchers may identify and test other factors or variables that can further define the effectiveness of the RAI video lesson.  Similar study may be conducted to explore the variables not included in this study, such as classroom.